A mediação de conflitos como via para uma cultura de paz, inclusão social e exercício da cidadania: as experiências de professores que atuaram na década de 1990 na Cidade Tiradentes - Zona Leste da Cidade de São Paulo - Fernandes, Magda Marly (2010)
This research studies the mediation of conflicts related to the political practice of the teaching actions, understood as the concrete pedagogical actions with socio-cultural impact and environmental change against the violences. The problems are the conflicts generally neglected and not pedagogically worked, perpetuating exclusionary mechanisms and an immobilist, alienating education. The objective is to understand the reasons and arguments that leaded the teachers to create pedagogical actions as means of conflicts solution. The individuals of this research are teachers that worked in the ninety decade, in Cidade Tiradentes São Paulo City East Zone. The geographic delimitation was chosen due to the fact that Cidade Tiradentes has the lower violence index in the region, despite the scarce resources of the development public politics, what opposes the social violence logic and instigates our eyes on the teachers performance. The time delimitation was a result of the information sources, the individuals profile, and the district historic reconstitution. The theme alignment was defined by the researcher reflection during the search for the education, violence, conflicts mediation and peace culture understanding, which configure the research chapters. The used method was a qualitative approach case study, with the researcher as a participant observer. For the interviews, a semi-structured questionnaire was applied from an itinerary organized around three dimensions: the work production, the political production, and the symbolic production of the investigated individuals. The results point to the understanding of the conflicts mediation, not only as a method with important techniques to be applied in a given context, but as the political action constitutive, therefore the ethics, in education